Strengthening Post-Ebola Health Systems : From Response to Resilience in Guinea, Liberia, and Sierra Leone - Govindaraj, Ramesh; Herbst, Christopher H.; Ajumobi, Oluwayemisi; Rockmore, Christophe; Zine Eddine El Idrissi, Moulay Driss; Workie, Netsanet; Clark, John Paul (Washington, DC: World Bank, 2017)
Strengthening Post-Ebola Health Systems addresses the challenge of enabling the development of viable, resilient, and fiscally sustainable health system in Guinea, Liberia, and Sierra Leone. Initiated while Ebola was still raging in all of the three most-affected countries in West Africa, it identifies the requirements for strengthening the health systems in these countries to go beyond just getting the number of Ebola cases to zero. The overall goal of this study is thus twofold: